Current practices in coffee post-harvest processing at Sitio San Roque, Pangantucan, Bukidnon - Ang, Lance Michael B.; Peralta, Justin Godfred B.
This study aimed to describe and document the current post-harvest practices for coffee at Sitio San Roque in Pangantucan, Bukidnon through on-site observations and an interview with the mill manager. This study also aimed to identify areas where process improvements may be implemented to improve overall coffee quality. The mill processes both Arabica and Robusta, from local farms and farms in neighboring provinces. The majority of coffee at this mill undergoes a washed process, wherein coffee cherries are mechanically pulped to remove outer layers, fermented and washed to break down and remove mucilage, and dried as parchment coffee on raised beds under a roofed structure. An estimated 10% of coffee is made defective during pulping, attributed to faulty pulping mechanization and subsequent over-fermentation as a result. Mill workers use bare hands and feet to agitate the coffee during washing, which may introduce unwanted microflora to the coffee. The endpoint of the drying process is estimated by the tactile feel of the coffee and validated by an electronic moisture meter. The coffee is sent to be hulled by the local cooperative. The final product, green coffee beans, is stored in jute sacks lined with GrainPro polyethylene bags, which preserve GCB quality by restricting atmosphere and moisture migration into and out of the packaging. The information generated in this study may be used in further studies to develop post-harvest interventions and technologies for improved output of the mill’s product.